Stability Improvement of Single Machine using ANFIS-PSS Based on Feedback-linearization - I Made Ginarsa; Osea Zebua (Universitas Ahmad Dahlan, 2014)
Electrical power system (EPS) operation always follows load changes which occur within time. Load changes and disturbances cause EPS operation to find a new balance point and before can reach the new balance point, the rotor speed will swing around its synchronous speed. This phenomenon causes the stability of the EPS operation decrease significantly, moreover, when the disturbance is large the machine tend to become unstable. To overcome this problem, it is necessary to add a power system stabilizer (PSS). This research proposes ANFIS-PSS based on feedback-linearization to stabilize the EPS operation. Feedback-linearization is a nonlinear control technique which feedback and limits several outputs in order to make the nonlinear system acts as a linear system. Data from conventional PSS is used to train and to update ANFIS-PSS parameters. Simulation results show an improvement of the stability of single machine model such as decreasing in maximum magnitude of rotor speed at the value of 0.466 rad/s and to reduce the time settling to 5.6 s.